2009
DOI: 10.1111/j.1464-410x.2008.08033.x
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of advanced age in patients with bladder cancer treated with radical cystectomy

Abstract: OBJECTIVETo evaluate the association of patient age with pathological and long‐term oncological outcomes after radical cystectomy (RC) for bladder carcinoma, as this disease, like many others, increases in incidence with age.PATIENTS AND METHODSWe retrospectively reviewed 241 consecutive patients with invasive bladder cancer who had RC between 1990 and 2007. The age at RC was analysed both as a continuous and categorical (≤50 years, 38 patients; 51–69, 172; or ≥70, 31) variable. Survival was also analysed.RESU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 19 publications
0
11
1
1
Order By: Relevance
“…In contrast, previous studies have shown 46%-55% rates of noneorgan-confined disease in elderly patients. 4,25 Conversely, fewer patients were found to have superficial or absent disease at cystectomy in this cohort than in previous studies. In the elderly, Nielsen et al 4 showed that 32% of cystectomy specimens harbored noninvasive disease.…”
Section: Discussioncontrasting
confidence: 61%
“…In contrast, previous studies have shown 46%-55% rates of noneorgan-confined disease in elderly patients. 4,25 Conversely, fewer patients were found to have superficial or absent disease at cystectomy in this cohort than in previous studies. In the elderly, Nielsen et al 4 showed that 32% of cystectomy specimens harbored noninvasive disease.…”
Section: Discussioncontrasting
confidence: 61%
“…It is reported that the tumor is more differentiated and less aggressive in bladder tumor patients younger than 40 years of age (28,29). In addition, other studies reported decreased recurrence and progression rates in younger patients as well (28,29,30,31,32). As opposed to this, there are also other studies that showed no significant difference between age (33,34,35).…”
Section: Discussionmentioning
confidence: 94%
“…The progress in technology and health care has contributed to increased life expectancy, and consequently there has been a disproportionate increase in the incidence of bladder cancer among elderly people [3]. Between 20 and 40% of patients with bladder carcinoma will develop a MIBC [6], with the consequences for the patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%